Self-medication: a current self-care practice amongst tertiary college students - Muiru, Hannah W. (International Journal Of Community Medicine And Public Health, 2023)
Background: Self-medication is the action of taking medication without consulting a physician or healthcare professional. It is one element of self-care coupled with social support during unwellness and aid. Though advocated for by health promoters it has its own fair share of cons. Methods: A descriptive cross-sectional study was conducted where a sample was obtained using published tables and simple random sampling technique was used to draw the sample from a population of 800 student’s gaining a total sample of 267 and to account for non-response and loss 10% was added giving a total of 294 respondents. Results: The prevalence was 82.6% (218) and the age group with the highest frequency of 77.4% was 19-21 years. The male prevalence was higher than for the female with 60.1% (131). The study revealed highest source of information to be pharmacist with 37.8%, highest source of medication was drug shops with 38.1%, highest used medication to be coughs and cold syrups with 78% (205). The reason for self-medication with the highest percentage was suffering from minor illness with 75.37% (199). The symptoms that are highly self-medicated for were coughs and cold (78.7%), pains and headaches (74.2%), stomach discomforts (72.4) and fever (70%). Conclusions: This study revealed a high prevalence of self-medication with 82.6% among the students. Creating awareness, enforcing the laws, informing the relevant stakeholders on availability of medicines and sealing the loops on dispensing of medication could save a generation.